Health and Clinical Management – Maximising Health Care Efficiency for Better Outcomes - Kubias, D.; Section Editor for the IMIA Yearbook Section on Health and Clinical Management (Yearbook of Medical Informatics, 2010)
Objectives: To present some of last year’s best papers in the field of health and clinical management.Method: Synopsis of the best articles selected for the IMIA Yearbook 2010.Results: All five selected articles present promising results, each in a different subtopic of health care management. From automated clinical syndrome detection to global population surveillance, through improving alerting systems’ impact, the selected articles should give an idea of how IT, not only can, but how it does help in health care management.Conclusions: While some people fear that computers might, one day, replace humans in health care, this is very far from being the case. What literature shows is that IT merely provides health care professionals with valuable tools that let them spend more time with their patients, prevent them from missing critical information, support them in their decision making and thus help improve their efficiency.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; decision support systems; management; patient care management; public health informatics